ROLE OF ACUTE PAIN WHEN ACHIEVING CUFFING POSITION USING MEANS OF RESTRAINT - Milosavljević, Srđan; Drljačić, Dragana; Srećković, Sreten (Sport - nauka i praksa, 2022)
The paper indicates the role and importance of acute pain during the operation of cuffing. The application of means of restraint from the space of physical strength, which usually precedes the activity of cuffing, requires a good knowledge of individual fighting techniques, and especially levers which serve to bring the person into the cuffing position by creating the feeling of acute pain. In that sense, lever is a good choice, because by executing lever, a person can be kept under control both for a shorter and a longer period of time, i.e. as long as it takes for cuffing to be performed safely. For that reason, it is important to know and distinguish the factors that define the individual value of each lever: possible level of infliction of pain (availability of body part, possibility of precise support, required level of force, time required for realization, etc.), as well as basic consequences of lever application. The applied lever, whose execution is harmonized with the previously mentioned factors, will produce sufficiently intense acute pain. Pain is an unpleasant sensory or emotional experience that is caused by potential or existing tissue damage or one that is described in words that would correspond to the said damage.
Keywords: pain; physical strength; establishing control; lever; special forces